A Re-examination of the Effect of Attitude, Religiosity, Self- Efficacy, and Moral Obligation on the Compliance Behavior of Income Zakat - HAJI-OTHMAN, YUSUF; YUSUFF, MOHD SHOLEH SHEH; LATIB, MOHD FARID ABD. (The journal of contemporary issues in business and government, 2021)
Despite a religious decree on the compulsory position of zakat on employment income in Malaysia, many Muslims still fail to fulfill their religious obligation to pay. Although there has been an increasing trend in the collection of business zakat, paddy zakat, and income zakat, there were some Muslims in Kedah who have not paid zakat to Kedah State Zakat Board (KSZB) so much so that the present increase in the collection of zakat is still not sufficient for distribution to all zakat recipients because of the increasing number of zakat asnaf (Haji-Othman, 2017). There is a rising trend in the collection of zakat. Yet, it is still insufficient to cover all zakat recipients, reflecting the efficiency (or the lack of it) of the Kedah State Zakat Board (KSZB) management. Studies on zakat compliance have shown mixed and inconclusive evidence regarding the determinants of income zakat compliance. Therefore, this study reexamines the effects of attitude, religiosity, self-efficacy, and moral obligations on the compliance behavior of income zakat in Kedah. This study employs the quantitative approach; primary data is collected using questionnaires to determine significant determinants of compliance behavior of income zakat. This study provides empirical evidence that attitude, religiosity, self-efficacy, and moral obligation are significant determinants of compliance behavior of income zakat in Kedah. This study is hoped to provide evidence that could be used as guidance for suitable policy and measures by Kedah State Zakat Board to improve zakat collection in the future.